2015
DOI: 10.5598/imafungus.2015.06.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic placement of Itajahya: An unusual Jacaranda fungal associate

Abstract: Itajahya is a member of Phallales (Agaricomycetes), which, based on the presence of a calyptra and DNA sequence data for I. rosea, has recently been raised to generic status from a subgenus of Phallus. The type species of the genus, I. galericulata, is commonly known as the Jacaranda stinkhorn in Pretoria, South Africa, which is the only area where the fungus is known outside the Americas. The common name is derived from its association with the South American originating Jacaranda mimosifolia trees in the cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Ge & A. Jacobs, were described based on morphology and DNA sequences of the ITS, partial LSU, the second largest subunit of RNA polymerase II (rpb2) and translation elongation factor 1-α (tef1) sequences (Ge et al 2018). The jacaranda stinkhorn (Itajahya galericulata Möller) in Pretoria was also typed phylogenetically (Marincowitz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Ge & A. Jacobs, were described based on morphology and DNA sequences of the ITS, partial LSU, the second largest subunit of RNA polymerase II (rpb2) and translation elongation factor 1-α (tef1) sequences (Ge et al 2018). The jacaranda stinkhorn (Itajahya galericulata Möller) in Pretoria was also typed phylogenetically (Marincowitz et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The fragments were purified using Ilustra ExoProStar (GE Healthcare) and then sequenced using the Big Dye Terminator Cycle Sequencing Kit (Applied Biosystems) with the same primer pairs. After sequencing, some ITS electropherograms presented double peaks; in order to resolve these, the ITS PCR fragments were cloned following Marincowitz et al (2015). All ribotypes were included in the phylogenetic analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Kreisel (1996) considered that the importance of an indusium for the taxonomy of the genus was overestimated, hence he downgraded Dictyophora to a section of Phallus . More recently, with the introduction of molecular data to the systematics and taxonomy of fungi, studies have shown that the indusium is a recurrent character, which independently emerged several times during the evolution of the group (Hosaka et al 2006, Cabral et al 2012, Marincowitz et al 2015, Trierveiler-Pereira et al 2017). Today, P. indusiatus Vent.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa, it was found to be associated with litter of J. mimosifolia [23]. Itajahya rosea as a rare species characteristic of desert and semiarid regions, as reported from Yemen and Northeastern Brazil [8,24,25].…”
Section: Discussionmentioning
confidence: 80%
“…Itajahya galericulata has been documented in dry sandy environments of New Mexico and Arizona in Brazil either in clay banks of forest streams or among roots of dead trees [ 6 , 22 ]. In contrast, in South Africa, it was found to be associated with litter of J. mimosifolia [ 23 ]. Itajahya rosea as a rare species characteristic of desert and semiarid regions, as reported from Yemen and Northeastern Brazil [ 8 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%